2008
DOI: 10.1007/s00125-008-1174-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of liver X receptors inhibits pancreatic islet beta cell proliferation through cell cycle arrest

Abstract: Aims/hypothesis Liver X receptors (LXRs) are important transcriptional regulators of lipid homeostasis and proliferation in several cell types. However, the roles of LXRs in pancreatic beta cells have not been fully established. The aim of this study was to investigate the effects of LXRs on pancreatic beta cell proliferation. Methods Gene expression was analysed using real-time RT-PCR. Transient transfection and reporter gene assays were used to determine the transcriptional activity of LXRs in pancreatic bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…1a, b). In agreement with our findings, the study by Meng et al also showed a significant upregulation of LXRs by the addition of LXR agonists to mouse beta cells [37]. Furthermore, we showed that GW3965 significantly induced the expression of the typical LXR lipogenic target gene, SREBP-1c, as well as the cholesterol efflux genes ABCA1 and ABCG1 in LPSstimulated islets (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1a, b). In agreement with our findings, the study by Meng et al also showed a significant upregulation of LXRs by the addition of LXR agonists to mouse beta cells [37]. Furthermore, we showed that GW3965 significantly induced the expression of the typical LXR lipogenic target gene, SREBP-1c, as well as the cholesterol efflux genes ABCA1 and ABCG1 in LPSstimulated islets (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we cannot rule out species-specific differences in the effects of LXRs, as murine islets or murine insulinoma cells were used by Choe et al [30] and Wente et al [40] whereas human pancreatic islets were used in our experiment. Such species differences may apply to pancreatic islets [27,37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work demonstrated that activation of the LXR pathway takes place after phagocytosis of apoptotic bodies (40), and apoptotic uptake is known to inhibit the proliferation of macrophages in response to M-CSF (41), which raises the question of whether this effect is mediated through production of LXR ligands. LXR agonists have been demonstrated to exert antiproliferative actions in other cellular systems as well, including vascular smooth muscle cells (21), prostate (38), and breast (22) cancer cells, T lymphocytes (20), and pancreatic islet b cells (42). While this work was under revision, Kim et al (43) also demonstrated antiproliferative effects of LXR agonists in several other cell lines, including human THP-1 macrophages.…”
Section: Discussionmentioning
confidence: 89%
“…This degradation stimulates the cleavage of mitochondrial BCL family proteins involved in apoptosis through cytoplasmic cytochrome c release (Yang and Sinensky, 2000;Rusinol et al, 2004). Oxysterols have also been identified as inducing apoptosis in a wide range of models such as human leukemia cell lines (Laffitte et al, 2003) or pancreatic b-cells (Choe et al, 2007;Meng et al, 2009). In these cells, the master lipogenic genes SREBP1c, fatty acid synthase and acyl CoA-carboxylase-a drive an increase in intracellular lipid accumulation, which results in cell lipotoxicity.…”
Section: Sanchez Et Al 2004) Covalent Binding Of Choles-mentioning
confidence: 99%